2015
DOI: 10.1093/cvr/cvv168
|View full text |Cite
|
Sign up to set email alerts
|

Human epicardial cell-conditioned medium contains HGF/IgG complexes that phosphorylate RYK and protect against vascular injury

Abstract: Early treatment with HGF/IgG complexes after myocardial ischaemia with reperfusion may rescue tissue through vasoprotection conferred by c-Met and RYK signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…Stem cells secrete potent combinations of cytokines, growth factors, enzymes, microvesicles/exosomes and genetic material, which help cardiac repair and regeneration at multiple points. The stem cell secretome supports cardiomyocyte survival and proliferation, differentiation of resident stem cells, and neovascularization, while limiting inflammatory and pro-fibrotic processes ( Baraniak and McDevitt, 2010 , Gnecchi et al, 2005 , Rao et al, 2015 , Zhou et al, 2011 ). Some paracrine factors have pleiotropic actions.…”
Section: Generation Of a Therapeutic Product From Stem Cell Secretomementioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells secrete potent combinations of cytokines, growth factors, enzymes, microvesicles/exosomes and genetic material, which help cardiac repair and regeneration at multiple points. The stem cell secretome supports cardiomyocyte survival and proliferation, differentiation of resident stem cells, and neovascularization, while limiting inflammatory and pro-fibrotic processes ( Baraniak and McDevitt, 2010 , Gnecchi et al, 2005 , Rao et al, 2015 , Zhou et al, 2011 ). Some paracrine factors have pleiotropic actions.…”
Section: Generation Of a Therapeutic Product From Stem Cell Secretomementioning
confidence: 99%
“…However, there are also paracrine factors that boost specific responses, thereby providing a more defined approach for selective treatments inspired by the stem cell secretome. For instance, mesenchymal stem cell-derived Insulin Growth Factor-1 (IGF-1) and ABI Family Member 3 Binding Protein (Abi3bp) reportedly induce resident CSC mobilization ( Mourkioti & Rosenthal, 2005 ) and differentiation to the cardiac lineage, ( Engels et al, 2014 , Hodgkinson et al, 2014 ) while CSC-derived basic Fibroblast Growth Factor (bFGF), Vascular Growth Factor-A (VEGF-A) and Hepatocyte Growth Factor (HGF) exert potent pro-angiogenic effects ( Rao et al, 2015 , Zhou et al, 2011 ).…”
Section: Generation Of a Therapeutic Product From Stem Cell Secretomementioning
confidence: 99%
“…By ELISA, we detected numerous, potentially beneficial factors secreted by human EPDCs including HGF, VEGFA, SDF-1, and angiopoietin-1 [80]. Notably, in cell protection assays of primary cardiac artery endothelial cells that were exposed to simulated ischemia (nutrient deprivation and hypoxia; 1% oxygen), only removal of HGF from EPI CdM was found to significantly reduce its cytoprotective effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we observed that about 30% of the HGF in human epicardial cell conditioned medium associated with polyclonal IgG into unique complexes that stimulated the RYK (related to tyrosine kinase) receptor in endothelial cells as well as c-Met (i.e. HGF receptor); these complexes conferred greater protection during hypoxia relative to HGF alone [80]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation